2023
DOI: 10.1038/s41390-023-02485-6
|View full text |Cite
|
Sign up to set email alerts
|

Preschooler screen time and temperamental anger/frustration during the COVID-19 pandemic

Abstract: Background In the context of increased media use and family distress during the pandemic, we examine whether preschooler screen time at age 3.5 contributes to later expressions of anger/frustration at 4.5, while also considering the inverse association. Methods Data are from a cohort of 315 Canadian preschool-aged children during the COVID-19 pandemic. Parent-reported measures included child h/day of screen time and child temperamental anger/frustration, both measured a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…However, the association between screen media and a child's temperament is likely to be bidirectional. While parents are likely to expose more difficult infants and toddlers to more screen time to regulate children's behavior (Radesky et al., 2016), excessive screen time has also negative effects on a child's emotional regulation (Fitzpatrick et al., 2022, 2023). For example, Fitzpatrick et al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the association between screen media and a child's temperament is likely to be bidirectional. While parents are likely to expose more difficult infants and toddlers to more screen time to regulate children's behavior (Radesky et al., 2016), excessive screen time has also negative effects on a child's emotional regulation (Fitzpatrick et al., 2022, 2023). For example, Fitzpatrick et al.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Fitzpatrick et al. (2022, 2023) who studied preschoolers' screen use during the COVID‐19 pandemic found that children's screen time at age 3.5 years predicted increased proneness to anger/frustration and decreased effortful control at age 4.5 years. Another possible explanation for our findings is that the association between screen time and a child's temperament is explained by other sociocultural factors, such as rules around screen time, parenting style, and parenting stress (Leppänen et al., 2020; Shin et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research examining young children's screen media use and externalizing behavior problems is complex but suggests that screen media use and children's behavior are linked in important and potentially bidirectional ways (Cliff et al., 2018; Radesky et al., 2023). Much of the research has examined duration of exposure to screen media ( screen time ), with studies finding significant links between screen time and subsequent externalizing behavior problems (for reviews, see Eirich et al., 2022, Li et al., 2020; see also Fitzpatrick et al., 2023; McNeill et al., 2019; Parkes et al., 2013; Poulain et al., 2018), though some findings are mixed (Neville et al., 2021; Peralta et al., 2018). Theoretically, exposure to screen media in early childhood may displace enriching and positive interactions and activities and result in fewer opportunities for young children to develop and practice self‐regulation and self‐soothing (the displacement hypothesis; e.g., Hornik, 1981), which may manifest in increased behavioral difficulties.…”
Section: Screen Media Use and Young Children's Externalizing Behavior...mentioning
confidence: 99%